Microwave memristive behavior in split-ring resonator metamaterials. (24th June 2016) - Wu, H Y; Shi, S K; Wang, C H; Jiang, X J; Yu, G; Qin, G Q; Fu, H; Zhou, J
Abstract: Photonic memristors, which behave as memristors operating with electromagnetic fields, present an effective means to achieve all-optical networking, and can promote the development of optical communications and computer technology. In this paper, we report a microwave memristive phenomenon at room temperature in metamaterials consisting of negative temperature coefficient thermistor ceramic disk and split-ring resonator (SRR). Hysteretic transmission-incident field power loops, the area of which varies with the scan rate of power, (similar to the fingerprint of memristors) were observed in the metamaterials. These effects are attributed to the increasing conductivity of the ceramic disk with increasing temperature generated by the interaction between electromagnetic waves and metamaterials. This work offers new opportunities for the development of photonic memristors.